PENGUATAN PENDIDIKAN KARAKTER BERBASIS BUDAYA SEKOLAH MELALUI PROGRAM LITERASI DASAR DI SEKOLAH DASAR NEGERI PONTIANAK - Herwulan Irine Purnama; Marzuki Marzuki; Sri Utami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
In building a golden generation equipped with 21st century skills, Basic Literacy is one of the activities in strengthening character education based on school culture. Reading and writing are two different literacy activities, but they are closely related and inseparable. This study aims to determine the strengthening of school culture-based character education through the basic literacy program at the 37 Southeast Pontianak State Elementary School. This study uses a qualitative approach. The location of this research was carried out at SDN 37 Southeast Pontianak. In this study to obtain primary data by directly interviewing and observing principals, teachers and students. The secondary data in this study were the PPK guide book at SDN 37 Southeast Pontianak, RPP, Curriculum, Vision and Mission of the school. Data collection techniques used in this research are observation, interview, and documentation data collection. The analytical technique that will be used in this research is an interactive model data analysis according to Miles & Huberman. The technique used to track credibility in this study uses triangulation techniques. The results of this study are the evaluation of learning strengthening character education through basic literacy programs for teachers in grades 1 and IV is carried out through authentic assessments, which include process assessments and assessments of learning outcomes. Process assessment is carried out during the learning process both inside and outside the classroom. While the assessment of learning outcomes is carried out after carrying out the learning process. There are two ways of character assessment carried out in this basic literacy-based KDP school, namely through observation and portfolios.Keywords: Character Building, School Culture, Basic Literature Program